PENGARUH DIGITAL MARKETING INSTAGRAM DAN TIKTOK TERHADAP KUNJUNGAN WISATAWAN SUNGAI MARANTING, BALANGAN - Norrahmiati; Devytasari Vanya Rosa (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2026)
This study aims to analyze the effect of digital marketing through Instagram and TikTok on the number of tourist visits at Sungai Maranting Tourist Attraction, Balangan Regency, both partially and simultaneously. This study used a quantitative approach with an associative method. Primary data were collected through questionnaires distributed to 100 respondents using purposive sampling technique. Data were analyzed using descriptive and inferential statistics, including multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that Instagram had a significant effect on tourist visits (regression coefficient 0.425; sig. 0.000) and TikTok also had a significant effect (regression coefficient 0.395; sig. 0.000). Simultaneously, Instagram and TikTok had a significant effect on tourist visits (F-test 94.017; sig. 0.000) with a coefficient of determination (R²) of 0.660, indicating that 66% of the variation in tourist visits can be explained by both variables. In conclusion, digital marketing through Instagram and TikTok plays an important role in increasing tourist visits, thus optimizing the use of social media is essential to promote tourism